Current status of phenolic pollution in urban lakes and its toxicity to cells – A case study of Xi’an, China - Min Wang; Yutong Zhang; Jingxin Sun; Chen Huang; Hongqin Zhai (Archives of Environmental Protection, 2023)
Liquid chromatography-mass spectrometry was used to detect and analyze phenolic compounds in the surface waters of four urban lakes in Xi’an – Hancheng Lake, Xingqing Lake, Nanhu Lake, and Taohuatan Lake. A total of 5 phenolic compounds were detected from the water samples, with a concentration range of ND-100.32 ng/L, of which bisphenol A (BPA) and nonyl phenol (NP) were the main types of phenolic compounds pollution in the four lakes. Pearson correlation analysis was used to analyze the concentration of phenolic compounds in the lake waters of Xi’an City and the water quality indicators COD, TP, NH3-N, DO, and pH during the same period. It was found that there was a significant positive relationship between the concentration of BPA and COD, the concentration of estradiol (17-beta-E2), estrone (E1) and TP and TN, the concentration of octylphenol (4-t-OP) and pH. The ecological risk assessment (ERA) shows that the concentration of BPA, 4-t-OP and NP in the lakes is at a medium risk level( is between 0.1–1), and that of E1 is at a high risk level (is greater than 1). Female cells (breast cancer cells) and male germ cells (testis cells) of mice were used as research objects to explore BPA and NP Toxic effect on mouse germ cells. BPA and NP at a concentration of 10-8 mol/L were found to have the most value-inducing effect on MCF-7 breast cancer cells positive for estrogen receptor. Obviously, both BPA and NP can induce the proliferation of testicular Sertoli cells